Deep-sea mining: interdisciplinary research on potential environmental, legal, economic, and societal implications - Koschinsky-Fritsche, Andrea; Werner, Welf (Integrated environmental assessment and management, 2018)
In this paper, we present a comprehensive overview of the current state of knowledge in the aforementioned fields as well as a comparison of the impacts associated with conventional terrestrial mining. Furthermore, we identify knowledge gaps that should be urgently addressed to ensure that the world at large benefits from safe, efficient, and environmentally sound mining procedures.